2017
DOI: 10.1016/j.ophtha.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Evicel versus Tisseel versus Sutures for Attaching Conjunctival Autograft in Pterygium Surgery

Abstract: Tisseel fibrin glue for the repositioning of conjunctival autografts in pterygium surgery was associated with a similar functional outcome as that of Vicryl sutures in terms of VA and SIRC. Pterygium recurrence, patient discomfort level, and surgery time were reduced markedly, as were flap dislocation and pterygium recurrence with Tisseel fibrin glue compared with Evicel fibrin glue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 19 publications
0
20
0
8
Order By: Relevance
“…Previous reported recurrence rate was 3.3-18.5% for experienced surgeons 6 , and 10-82% for trainees 8,15 . The lower recurrence rate in this study can be attributed to two reasons: CAG transplantation has been shown to be superior to bare sclera technique or AMT 4,9,10 , with respect to recurrence, and in all cases we used fibrin glue, which is associated with lower recurrence compared to sutures 38 .…”
Section: Discussionmentioning
confidence: 73%
“…Previous reported recurrence rate was 3.3-18.5% for experienced surgeons 6 , and 10-82% for trainees 8,15 . The lower recurrence rate in this study can be attributed to two reasons: CAG transplantation has been shown to be superior to bare sclera technique or AMT 4,9,10 , with respect to recurrence, and in all cases we used fibrin glue, which is associated with lower recurrence compared to sutures 38 .…”
Section: Discussionmentioning
confidence: 73%
“…In a study by zloto et al, the recurrence rate was 17.24 in the suture group whereas in our study the recurrence rate was 2.89%. [ 18 ] Conjunctival edema was seen in 122 (70.52%) in Group 1, 151 (43.02%) in Group 2, and 139 (88.54%) in Group 3. Granuloma formation was seen in 2 (1.16%) in Group 1, no patients in Group 2, and 1 (0.64%) in Group 3.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical techniques have evolved from bare sclera technique, autorotation of conjunctival graft, use of amniotic membrane graft to the development of conjunctivo-limbal autograft 4,5,6 . One of the popular techniques used is excision of pterygium is covering the defect with conjunctival autograft, which is either sutured or fixed with fibrin glue 7 . Fixing the graft with fibrin glue reduces operative time, gives good cosmetic results and causes less post operative discomfort however like any other surgical procedure it has some disadvantages like increased cost, graft loss, granuloma formation and transmission of infection to mention a few.…”
Section: Introductionmentioning
confidence: 99%